2016
DOI: 10.1007/s13760-016-0662-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection superiority of 7 T MRI protocol in patients with epilepsy and suspected focal cortical dysplasia

Abstract: In 11 adult patients with suspicion of Focal cortical dysplasia (FCD) on 1.5 T (n = 1) or 3 T (n = 10) magnetic resonance imaging (MRI), 7 T MRI was performed. Visibility, extent, morphological features and delineation were independently rated and subsequently discussed by three observers. Additionally, head-to-head comparisons with corresponding 3 T images were made in the eight patients with a previous 3 T MRI and sustained suspicion of FCD. Comparison with histopathology was done in the five patients that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…We hypothesize that a similar effect can be gained from 7 T, by virtue of increased signal‐to‐noise ratio, allowing higher resolution and contrast . Dysplastic lesions previously detected using lower‐field MRI are reported to be detected with more confidence and visualized in greater detail at 7 T . One previous study reported an improved detection rate of 7 T MRI compared to lower‐field MRI, although half of the patients in whom a new lesion was detected at 7 T underwent previous scanning in presurgical evaluation at only 1.5 T, and not at 3 T, the field strength currently considered optimal …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that a similar effect can be gained from 7 T, by virtue of increased signal‐to‐noise ratio, allowing higher resolution and contrast . Dysplastic lesions previously detected using lower‐field MRI are reported to be detected with more confidence and visualized in greater detail at 7 T . One previous study reported an improved detection rate of 7 T MRI compared to lower‐field MRI, although half of the patients in whom a new lesion was detected at 7 T underwent previous scanning in presurgical evaluation at only 1.5 T, and not at 3 T, the field strength currently considered optimal …”
mentioning
confidence: 99%
“…18 Studies comparing 1.5 and 3 T MRI in epilepsy surgery candidates have shown that imaging at 3 T can identify FCDs that escaped detection at 1.5 T. [19][20][21][22] In a cohort of patients with FCD type II, 3 T MRI showed a lesion in 20% of patients with nonlesional 1.5 T. 22 We hypothesize that a similar effect can be gained from 7 T, by virtue of increased signal-to-noise ratio, allowing higher resolution and contrast. 23 Dysplastic lesions previously detected using lower-field MRI are reported to be detected with more confidence and visualized in greater detail at 7 T. 24 One previous study reported an improved detection rate of 7 T MRI compared to lower-field MRI, although half of the patients in whom a new lesion was detected at 7 T underwent previous scanning in presurgical evaluation at only 1.5 T, and not at 3 T, the field strength currently considered optimal. 25 In our study we aim for verification of the clinical value in a larger group of patients, of whom most underwent previous 3 T MRI, and using a full three-dimensional (3D) scanning protocol with submillimeter resolutions in fluid attenuated inversion recovery (FLAIR), T 1 , T 2 , and T 2 *weighted, and white matter suppression sequences.…”
mentioning
confidence: 99%
“…The acquisition protocol comprised four sequences, only MP2RAGE and SWI will be discussed in this paper: (1) a 3D MP2RAGE sequence with .6 mm isotropic spatial resolution, 192 × 192 × 154 mm (whole‐brain) field‐of‐view (FOV), TE/TI 1 /TI 2 /TR = 2.05/800/2,700/6,000 milliseconds, α 1 / α 2 = 7°/5°, 240 Hz/Px bandwidth, 3 × GeneRalized Autocalibrating Partial Parallel Acquisition (GRAPPA) acceleration in the first phase‐encoding direction and 6/8 partial Fourier undersampling in both phase‐encoding directions, and a total acquisition time of approximately 10 minutes; (2) a flow‐compensated 3D GRE‐based SWI sequence with .375 × .375 × 1 mm resolution, 197 × 197 × 40 mm FOV (axial slab), TE/TR = 20/28 milliseconds, α = 10°, 120 Hz/Px bandwidth, 2 × GRAPPA acceleration and 6/8 partial Fourier undersampling in the first phase‐encoding direction, and a total acquisition time of approximately 4 minutes; (3) diffusion tensor imaging (DTI) with a voxel size of 1.5 × 1.5 × 1.5 mm,…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, ultra‐high‐field (UHF) 7T MRI machines have been available in a few research centers for in vivo human brain imaging. The increased signal‐to‐noise ratio, improved spatial structural resolution, and enhanced image contrast allow for better depiction, characterization, and visualization of millimetric anatomical structures and lesions such as FCD than 3T that offers the chance to reveal new features of neurological diseases that may change clinical diagnosis . Among sequences specifically designed for higher magnetic fields, magnetization‐prepared two rapid acquisition gradient echoes (MP2RAGE) is a 3‐dimensional T1‐weighted sequence with strong contrast between gray and white matter and minimal effect of B1 inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefor, 7 T MRI yields the promise of improving detection. In epilepsy patients, ex vivo [19] and in vivo 7T MRI examples of FCD in humans are available [20][21][22].…”
Section: Introductionmentioning
confidence: 99%